Üzümçülükdə istifadə edilən xırdalayıcı-cecəayıran maşının nar gilələnməsi üçün təkmilləşdirilməsi və tədqiqi - Quliyeva, Nərmin; Vələdov, Mahmudnəbi; Babayeva, Lamiyə; Mürsəlov, Elman (My University, 2024)
The roller crusher machine designed for grapes has been improved for pomegranate processing. The critical speeds of the machine that separates the seeds of pomegranate fruits from the peel have been determined. The potential for increasing the productivity of such machines has been noted.
Improvement and research of a crushing-destemming machine used in viticulture for pomegranate crushing
Keywords: Crushing and seed separating machines; Pomegranate seed separating machines